PENGARUH PENGGUNAAN SOSIAL MEDIA TIKTOK KONTEN RELIGI TERHADAP PEMBENTUKAN KARAKTER SOPAN SANTUN SISWA KELAS XI SMA BINA INSANI BOGOR - Rahma Yuliasari; Indriya Indriya; Andri Ardiansyah (FIKRAH, 2024)
Along with the times, social media must be able to answer the needs of the community, especially for students. Where it makes students easy to access anything they want to know through the features that technology has offered at this time. Therefore, the influence of social media on the development of students' character is very possible, character building in students is a provision for the future of a country. The purpose of this study was to determine whether there is an influence on the use of social media tiktok religious content on the formation of the character of manners of class XI students at Bina Insani Bogor High School. This research uses descriptive quantitative. The data analysis used is a simple linear regression test. Based on the results of the analysis, the research shows that: (1) This study shows that the use of social media tiktok religious content on the formation of character manners of class XI students at Bina Insani Bogor High School. This is based on the results of the SPSS table output, where the significance level is P-value (0.003) < Sig (0.05), then Ho is rejected and Ha is accepted. Which means "influential", meaning that the use of social media tiktok religious content affects the character building of class XI students at Bina Insani Bogor High School.